1997
DOI: 10.1103/physrevb.55.7615
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence from mechanically milled Si andSiO2spowders

Abstract: The photoluminescence ͑PL͒ in as-received and milled Si and SiO 2 powder is reported. The Si and SiO 2 powder is characterized by chemical analysis, Raman scattering, x-ray photoelectron spectra, infrared absorption, x-ray diffraction, and differential thermal analysis. The results indicate that the Si powder has amorphous Si oxide and suboxide surface layers. The milling of Si powder results in the formation of nanocrystalline/ amorphous Si components. An amorphous SiO 2 component is formed by milling crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 54 publications
1
41
3
Order By: Relevance
“…Photoluminescence properties of silicon nanocrystals prepared by ball milling were previously studied by Shen et al 10 Here we present evidence of a smooth transition between bulk and nanocrystalline properties of silicon. By observation of defects characteristic for bulk crystal, we trace their behavior as slightly perturbed by volume restriction.…”
Section: Introductionmentioning
confidence: 52%
“…Photoluminescence properties of silicon nanocrystals prepared by ball milling were previously studied by Shen et al 10 Here we present evidence of a smooth transition between bulk and nanocrystalline properties of silicon. By observation of defects characteristic for bulk crystal, we trace their behavior as slightly perturbed by volume restriction.…”
Section: Introductionmentioning
confidence: 52%
“…For some cases, the powder becomes amorphous beyond this point. Furthermore, through a large amount of published research work on the amophization of pure elements such as Si, Ge, Se [16][17][18][19][20][21], it was found that the amorphisation process has been related to crystalline phase instability, related to a lattice expansion due to a critical crystallite size refinement induced by ball milling.…”
Section: Introductionmentioning
confidence: 98%
“…Although we have not done extensive research, we have found three papers in which this hypothesis should be taken into account. The first 21 reports a supralinear dependence of the radiation emitted by laser ablated porous silicon; the second 22 finds a pressure quenching of the radiative emission of mechanically milled Si and SiO 2 powders, and the third 23 analyzes the luminescence of porous silicon after a pulsed laser excitation. In this case, the spectra have a two-peak structure.…”
Section: Photoluminescence Of Porous Silicon and Related Materialsmentioning
confidence: 99%